Wahabisme dalam Perspektif Teologi Hassan Hanafi - Rasyidin, Yusafrida; Nofrizal, Nofrizal; Ajid, Abdul Husna (Universitas Islam Negeri Raden Intan Lampung, 2024)
Abstract;Wahabism as a reform movement in Islam has proven to be politically successful, and as a teaching, this movement has puritanical characteristics or seeks to purify Islamic teachings which it considers to have been distorted to suit the version of the teachings it brings. In this article, researchers will analyze Wahhabism from the perspective of a contemporary theologian, Hassan Hanafi. This research is literature-based (library research) and uses interpretive, philosophical descriptive methods. In Hassan Hanafi's view, Wahhabism is a theocentric and textualist theological school, their orientation is to submit and obey religious laws/texts which do not necessarily have any relevance to the reality of the Islamic world.Keywords:Hasan Hanafi; Theology; Wahabisme. Abstrak;Wahabisme sebagai suatu gerakan pembaharuan dalam Islam terbukti sukses secara politik, dan sebagai sebuah ajaran, gerakan ini memiliki karakteristik puritan atau berusaha memurnikan ajaran Islam yang ia anggap telah menyimpang agar sesuai dengan versi ajaran yang ia bawa. Dalam artikel ini, peneliti akan menganalisa Wahabisme dalam perspektif seorang teolog kontemporer, Hassan Hanafi. Penelitian ini tergolong dalam jenis penelitian kepustakaan, (library research) dan menggunakan metode interpretatif, deskriptif filosofis. Dalam pandangan Hassan Hanafi, Wahabisme adalah aliran teologi teosentris dan tekstualis, orientasi mereka ialah tunduk dan patuh terhadap turats/teks-teks keagamaan yang belum tentu ada relevansinya dengan realitas dunia Islam.Kata Kunci: Hasan Hanafi; Teologi; Wahabisme.